ASSESSMENT OF DIAGNOSTIC ACCURACY OF TRI-PHASIC COMPUTED TOMOGRAPHY IN DIFFERENTIATING BETWEEN CIRRHOSIS NODULES AND HEPTOCELLULAR CARCINOMA NODULES (The Research of Medical Science Review, 2025)
Hepatocellular carcinoma is basically a type of tumor originating from liver cells. In primary liver cancer, hepatocellular carcinoma is the most prevalent kind. The most frequent primary hepatic tumor, hepatocellular carcinoma ranks sixth globally interms of frequency of occurrence and can cause up to one million deaths yearly. Cirrhosis is a disease that leaves the liver permanently damaged and scarred. Cirrhosis is the term describing the histological development of regenerative nodules surrounded by fibrous bands as a result of chronic liver injury. The normal function of the liver is hampered by the replacement of healthy liver tissue with scar tissue. Computed Tomography (CT) scan is best for identifying and evaluating hepatic cancers. When contrast material is injected, multiphasic scanning with helical CT improves hepatocellular carcinoma detection and staging. The aim of this study was to assess the diagnostic accuracy of tri-phasic computed tomography in differentiating between cirrhotic nodules and hepatocellular carcinoma nodules. This was a cross -sectional study design. It was carried out in Arif Memorial Teaching Hospital. Non-probability convenient Sampling technique was used. Statistical analysis were conducted using SPSS version 26.0, with Receiver Operating Curve (ROC) and independent sample t- test was applied to assess the diagnostic accuracy of tri-phasic CT for differentiating both nodules. Initial finding of Area under curve (AUC)for a ROC curve value of 0.4 and independent sample t- test shows a 0.01 p. value for cirrhotic nodules while for hepatocellular  carcinoma nodules Area under curve (AUC)for a ROC curve shows a value of 0.9 and independent sample t- test shows a value of 0.8. According to my study results, AUC of a ROC curve analysis shows 0.4 value (less than 0.5) for cirrhotic nodules which means a true negative value while AUC for ROC curve analysis for HCC nodules shows a value of 0.9 which means a true positive results. In conclusion tri- phasic computed tomography has good diagnostic accuracy for hepatocellular carcinoma nodules as compared to cirrhotic nodules. This study improves the financial status of our country because CT is a costly modality. This study aligns with united nation sustainable development goal number 08 (decent work and economic growth).